2007
DOI: 10.1016/j.jcomdis.2007.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The role of central nervous system plasticity in tinnitus

Abstract: Tinnitus is a vexing disorder of hearing characterized by sound sensations originating in the head without any external stimulation. The specific etiology of these sensations is uncertain but frequently associated with hearing loss. The "neurophysiogical" model of tinnitus has enhanced appreciation of central nervous system (CNS) contributions. The model assumes that plastic changes in the primary and non-primary auditory pathways contribute to tinnitus with the former perhaps sustaining them, and the latter c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 80 publications
1
58
0
2
Order By: Relevance
“…It has been clearly demonstrated that tinnitus is generated in the central auditory system, possibly due to maladaptive cortical reorganization (3)(4)(5)(6)20). For instance, auditory cortex neurons that are deprived of normal thalamo-cortical input due to hearing loss do not become inactive, but "rewire" with excitatory inputs from neighboring neurons (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated that tinnitus is generated in the central auditory system, possibly due to maladaptive cortical reorganization (3)(4)(5)(6)20). For instance, auditory cortex neurons that are deprived of normal thalamo-cortical input due to hearing loss do not become inactive, but "rewire" with excitatory inputs from neighboring neurons (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Constitui-se uma morbidade importante que afeta diretamente a saúde e a vida social do indivíduo 15,26 , porém desconhecido no público pediátrico em idade escolar.…”
Section: Os Indivíduos Apresentamunclassified
“…Cortical map plasticity is induced by deafferentation in not only the somatosensory but also the visual and auditory systems (Merzenich et al, 1983;Calford, 2002). Photophobia is observed in patients with optic nerve injury (Kawasaki and Purvin, 2002), and damage to the inner hair cells produces tinnitus (Saunders, 2007). These sensory abnormalities may be comparable with neuropathic pain in the somatosensory system.…”
Section: Basal Firing In Sensory Nervesmentioning
confidence: 99%